Synthesis and radical scavenging activity of phenol–imidazole conjugates - Correia, Carla (2014)
Novel hydroxylated benzylideneamino imidazole derivatives were synthesized and their radical scavenging activity was assessed against DPPH and hydroxyl radicals. In the DPPH assay, most of the synthesized compounds showed an IC50 in the range 3.2 mu M <= IC50 <= 8.4 mu M, lower than the reference compound trolox (IC50 = 9.5 mu M) or the parent aldehydes (5.4 mu M <= IC50 <= 11.6 mu M). The activity depends mainly on the phenolic subunit (number and position of the hydroxyl groups) and the extent of conjugation with the imidazole ring. In the deoxyribose assay, all the compounds, including parent imidazoles and aldehydes, showed high activity against the hydroxyl radical and the ability to chelate iron ions. At 5 mu M concentration, the compounds protected the deoxyribose from degradation by hydroxyl radical between 62% and 38%. (C) 2014 Elsevier Ltd. All rights reserved.